Effect of Grafted Hydroquinone on the Acid-Base Properties of Poly(acrylic acid) in the Presence of Copper (II). (24th March 2015) - Bensacia, Nabila; Moulay, Saâd; Garin, François; Fechete, Ioana; Boos, Anne
Abstract : Potentiometric titration of poly(acrylic acid) and hydroquinone-functionalized poly(acrylic acid) was conducted in the presence of copper (II). The effects of hydroquinone functionalizing and copper (II) complexing on the potentiometric titration of poly(acrylic acid) were studied in an ionic environment and in its absence. Henderson-Hasselbalch equation was applied to assess its validity for this titration. Coordination number and the stability constants of the copper- (II-)complexed polymers were determined, and results showed the formation of mostly monodentate and bidentate copper- (II-)polymer complexes.